A Comparative Analysis of Hypocalcemia Incidence in Patients Undergoing Thyroidectomy: LigaSure Versus Conventional Ligation of Vessels by Knot Tying: Hypocalcemia in Thyroidectomy Patients: LigaSure Versus Conventional Ligation - Himayoun, Zain; Ather, Hunza Binte; Malik, Mudassar; Pervaiz, Numan; Ahmed, Iftikhar; Rahman, Usman Ali (Pakistan Journal of Health Sciences, 2025)
Hypocalcemia is a frequent postoperative complication after total thyroidectomy. It usually arises from unintentional injury to the parathyroid glands or disruption of their blood supply during surgery. Advanced vessel sealing technologies like LigaSure aim to lower this risk by ensuring greater surgical precision and reducing thermal injury to adjacent structures, particularly the parathyroid glands. Objectives: To compare the incidence of postoperative hypocalcemia between LigaSure and conventional knot-tying techniques in total thyroidectomy patients. Methods: A randomized controlled trial was conducted at the Surgical Department of Gulab Devi Hospital, Lahore, from April 2024 to March 2025. Seventy-six patients who underwent total thyroidectomy for benign thyroid disease were randomly allocated to the LigaSure (n=38) and conventional knot-tying (n=38) groups. Serum calcium levels were measured preoperatively and at 24/48 hours postoperatively. For statistical analysis, SPSS v24 was used, and non-parametric tests like the Mann-Whitney U and chi-square tests were used. Results: Incidence of hypocalcemia was higher in the LigaSure group (10.5%) as compared to the conventional group (7.9%), but of no statistical significance (p=0.692). Conclusions: Both techniques demonstrated comparable safety profiles with no statistically significant differences in postoperative outcomes. LigaSure offers a comparable alternative to conventional methods of vessel sealing/ligation.